A study on risk perception and portfolio management of equity investors in coimbatore city - K, Prabhakaran; P, Karthika (Journal of Management and Science, 2011)
Identifying key factors influencing individual investor’s decision to make portfolio choices is important to understand their different investment behavior. This paper explores individual investor’s preference for portfolio choices and provisionally investigates impacts of risk tolerance and risk perception on their investment decision. Specifically we decide socioeconomic status difference in investment preference for portfolio choices with respect to investor’s age, income level. Using chi-square analysis on investment experiments to obtain some evidences from a sample of 200 respondents in survey; our results indicate that investor’s decisions to make their portfolio choices are significantly and negatively related to personal income level. This finding implicates that investor with higher risk tolerance level shows higher likelihood to make their investment decision on portfolio choices it is found that male investor demonstrates much preference on portfolio choices with higher percentage of totalreturn.